Menschenrechtsbildung an Gymnasien Verständnisse, Chancen und Herausforderungen - Rinaldi, Stefanie (Verlag Barbara Budrich, 2018)
The author presents a comprehensive picture of teachers' subjective understandings, attitudes and beliefs about human rights education. From this, indications are derived as to how human rights education can be further developed pedagogically and methodologically and which institutional measures are necessary. In addition, ideas for the pedagogical implementation of human rights education are outlined.